The Role of Gender Identity in the Bullying Named Jadin in Joe Bell (2020) - Hudi Ermanto (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2023)
This study is aimed analyzing (1) the form of Bullying shown by bullies in Joe Bell movie (2) the impact of Bullying to the main Character in Joe Bell movie.The study uses descriptive qualitative method to analysis the film entitled Joe Bell directed Reinaldi Marcus Green as objective research. The collecting data, and selecting, the analyzing data of the research method by used displaying, explaining, The result of study : (1) the form of Bullying shown by bullies in Jadin character (2) the impact of bullying to the main character of Joe Bell as victims of the effects of bullying on their children, such as mental health disorders, and severe depression to the point where the effects of bullying were fatal and caused Jadin and Joe Bell to commit suicide.